Bostwick Consistometer as a visual quality control tool for thickened foods - Miranda Zamora, William Rolando (2020)
Design, build and measure Bostwick consistency of thickened foods at an objective level, since Bostwick consistency is critical for their quality control. This study examined the relationship of the extension or route in the Bostwick (that is, the distance that a liquid flows) for a variety of foods that are sold in the Sullana Market and determined whether the flow distance visually differentiated the thickness of food versus honey-like consistency. Four thickened products (mustard, dressing, mayonnaise and honey) purchased from the Sullana Market were tested. Measurements were recorded using the Bostwick consistometer. Bostwick consistencies of thickened and honey-like foods differed significantly in their degree of travel. Using our Bostwick consistometer, B10s: 13 cm in honey (83.95°Brix), B30s: 2.2 cm in mustard (12.3°Brix), B10s: 4.3 cm in mayonnaise (0.25°Brix) and dressing (7.5°Brix) that could not be made due to its consistency (very liquid, similar water consistency), none of the food measured has a consistency similar to honey. There was an inverse correlation between viscosity data and Bostwick consistency results.